Does College Education Reduce Small Business Failure? - Andrea Asoni; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2014)
We estimate the effect of college education on business survival using the NLSY79. The endogeneity of both education and business ownership is accounted for by a competing risks duration model augmented with a college selection equation. Contrary to the previous literature, we fi nd no effect of college education on business failure. College however signi cantly increases employment survival. Unlike college, cognitive skills have a positive impact on employment survival for both the self-employed and employees. The results suggest that college affects the self-employed and salaried employees in different ways, for example generating skills more useful in employment than self-employment.
Keywords: C41; J24; L26; 330; Selection; Entrepreneurship; College Education; Intelligence; Self-con dence